Melestarikan Event Dieng Culture Festival Sebagai Wujud Kearifan Lokal di Masyarakat Dataran Tinggi Dieng - Tri Yunita Sari; Heri Kurnia (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2023)
Local wisdom includes the outlook on life, knowledge, and life strategies implemented by the community in meeting their needs. Activities that reflect local wisdom include religious practices, culture, and customs. There are many variations of local wisdom in Indonesia because the people consist of various tribes and cultures. One example of an area that promotes culture and introduces history and philosophy through activities is Banjarnegara Regency, especially in the Dieng Highlands. In this area, an annual cultural festival known as Dieng Culture Festival is held, which showcases various arts and cultures. Cultural festivals such as Dieng Culture Festival are a good way to promote local wisdom, because they can attract the attention of people from various regions and even abroad. In addition, such activities can help local communities maintain their cultural heritage and introduce it to the younger generation. This research uses a literature review method that refers to various sources such as articles, journals, and other media. A narrative approach is used in compiling this review literature by grouping existing data and summarizing the analyzed content. This research resulted in information that Dieng, an area in Banjarnegara Regency, has an annual cultural festival known as Dieng Culture Festival. Dieng Culture Festival is an annual parade event that showcases local culture and wisdom. This event consists of several series, including: a) Jazz over the clouds and lantern festival, b) Traditional art performances, c) shadow puppet performances, d) Cultural relays, f) Dreadlocks shaving rituals, and so on.